ANALISIS REDUKSI GAS H2S UNTUK MENINGKATKAN KUALITAS BIOGAS BERBAHAN BAKU SAMPAH ORGANIK BUAHBUAHAN - Feti Eka Rahayu; Sunaryo Sunaryo (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
Biogas is flammable gas produced from the fermentation of organic material by anaerobic bacteria-bacteria. Component of biogas, among others, 50-75% CH4, 24-40% CO2 and Â± 2% H2S. Hydrogen sulfide in spite of small biogas but simply applied is corrosive, odorless and non-toxic, so it simply applied needs to be reduced in the biogas. The purpose of this research is to reduce H2S gas from biogas. For that, it needs a filter in the form of sand iron that had previously been through a process of refinement with a variation of the time of 5 minutes, 10 minutes, and 15 minutes. The gas formed in a balloon and taken to the laboratory for further test through Gas Analyzer to know the magnitude of the power filter adsorption of gas. After the test is finished, the Gas Analyzer can be analyzed how the power large iron sand filter adsorption of H2S gas. From the results of these tests, we can know the levels of H2S is reduced. Keywords: biogas, anaerob, H2S, Gas Analyzer, filter, adsorption